The Increased Channel Activity of N-Methyl-D-Aspartate Receptors at Extrasynaptic Sites in the Anterior Cingulate Cortex of Neonatal Rats Following Prolonged Ketamine Exposure - Jin J; Wang R; Lin Q (Journal of Pain Research, 2021)
Jianhui Jin,1,2 Ruirui Wang,2 Qing Lin2 1Department of pain Management, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Psychology, The University of Texas at Arlington, Arlington, TX, USACorrespondence: Qing LinDepartment of Psychology, The University of Texas at Arlington, Arlington, TX, 76019, USATel +1 817-272-0154Email qilin@uta.eduBackground: Ketamine is a dissociative anesthetic, commonly used for analgesia and anesthesia in a variety of pediatric procedures. It acts as a non-competitive antagonist to block ion channels of the N-methyl-D-aspartate receptors (NMDARs). Our previous study showed that repeated ketamine exposure developed a compensatory increase in NMDAR-mediated currents in neurons of the anterior cingulate cortex (ACC) of neonatal rats, and this increase was largely mediated by the GluN2B subunit-containing receptors, a predominant type of NMDARs during embryonic and early development of the brain. These data provide the molecular evidence to support that immature neurons are highly vulnerable to the development of apoptotic cell death after prolonged ketamine exposure.Methods: Using whole-cell patch-clamp electrophysiology in an in vitro preparation of rat forebrain slices containing the ACC, the present study aimed at further determining whether GluN2B-containing NMDARs at extrasynaptic sites of immature neurons were the major target of ketamine for developing a compensatory increase in NMDAR-mediated synaptic transmission.Results: Our major findings were that GluN2B subunits played a significant role in mediating ketamine-induced blockade of NMDAR-mediated currents in neonatal neurons and GluN2B-containing NMDARs expressed at extrasynaptic sites in neonatal neurons were the major player in compensatory enhancement of NMDAR-mediated currents after repeated ketamine exposure.Conclusion: These results provide new evidence to strongly indicate that GluN2B-containing NMDARs at extrasynaptic sites are the key molecule contributing to the high vulnerability of the neonatal brain to ketamine-induced neurotoxic effects.Keywords: immature neurons, ketamine, extrasynaptic NMDA receptors, GluN2B-containing NMDA receptors